2021
DOI: 10.17306/j.jard.2021.01374
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing value-addition agricultural choice within smallholder farming agribusinesses of Gauteng Province in South Africa

Abstract: This paper investigated factors influencing value addition agricultural choices of smallholder farming agribusinesses in the Gauteng Province, South Africa, using the Ordinary Least Squares regression model. The study used randomly sampled data collected from 102 smallholder farmers by the National Agricultural Marketing Council and the Gauteng Department of Agriculture and Rural Development. Four types of value addition were identified, namely postharvest, food preservation, milling, and post-slaughter. The r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 20 publications
0
10
0
2
Order By: Relevance
“…It is worth noting that studies by Proctor et al (2000) and Mthombeni et al (2021) state that most small-scale agro-processors are illiterate or semi-literate and have no formal training, and their sources of knowledge on processing and skills are apprenticeships. Melembe et al (2021) found that most farmers (54.9%) have secondary or high school education, while close to 20% have tertiary education, and less than 10% of the farmers in the study area are without formal education. These findings compare favourably with the findings of the current study.…”
Section: Descriptive Statisticsmentioning
confidence: 87%
“…It is worth noting that studies by Proctor et al (2000) and Mthombeni et al (2021) state that most small-scale agro-processors are illiterate or semi-literate and have no formal training, and their sources of knowledge on processing and skills are apprenticeships. Melembe et al (2021) found that most farmers (54.9%) have secondary or high school education, while close to 20% have tertiary education, and less than 10% of the farmers in the study area are without formal education. These findings compare favourably with the findings of the current study.…”
Section: Descriptive Statisticsmentioning
confidence: 87%
“…Europeans encourage and fund crossnational networking in research (Boonekamp et al, 1998). Small holder agro-business need to invest in training to increase the knowledge base of the organization (Melembe et al, 2021) Technology and innovation capability This study asserted the need for investment in technology and innovation hubs formulated on a bedrock of sound and favorable economic policies that promote agro-processing entrepreneurship. Asare & Essegbey (2016) confirmed and recommended the commercialization of technology development, innovation capability, and government investment.…”
Section: Knowledge Managementmentioning
confidence: 98%
“…Labor force and skill development Agro-processing and manufacturing industries should invest in continuous technical efficiency and technology know-how of their labor force. Training is confirmed to be essential to labor force skill development especially for small and medium agro-processing enterprises (Johnson et al, 2015;Melembe et al, 2021).…”
Section: Appendix a Data Extraction Table Appendix B Critical Apprais...mentioning
confidence: 99%
“…In terms of preventative and risk-based food manufacturing standards, institutional regimes such as CoPS are a prerequisite for offtake agreements which benefit small and medium agribusinesses struggling to implement systems due to low levels of tangible resources and technical capability (Manasoe et al, 2022). The compliance of agribusinesses with regulatory standards improves product credibility and fetches premium prices as consumers prefer to purchase certified and branded products (Ding and Veeman, 2019;Melembe et al, 2021). Research emphasises that many agro-processing businesses require the careful navigation of complex and sophisticated regulations that typically require extensive EC (Mmbengwa et al, 2020;Neves et al, 2019;Van Lin et al, 2018).…”
Section: Entrepreneurship and Agribusiness In The Context Of Regulationsmentioning
confidence: 99%
“…Studies indicate that value-added processing activities as value chain actions may either be nutritional, technological, or economic insofar as raw agriculture products undergo alterations into usable items such as food, fibre, fuel, and industrial raw materials (FAO, 2017;Kierczynska, 2019). Value may be added by agribusinesses in various forms such as quality, innovativeness, and cost advantage, where different value chain actors receive economic rents, and where value creation often hinges on entrepreneurship (Melembe et al, 2021;Ngarava, 2021;Owoseni and Adeyeye, 2012).…”
Section: Introductionmentioning
confidence: 99%